Cardiovascular risk assessment among rural population: findings from a cohort study in a peripheral region of Bangladesh. (August 2016) - Fatema, K.; Zwar, N.A.; Milton, A.H.; Rahman, B.; Awal, A.S.M.N.; Ali, L.
Abstract: Objectives: The incidences of non-communicable diseases including cardiovascular diseases (CVDs) is increasing in Bangladesh. The reasons for this increasing trend need to be explored. The aim of this study is to assess the risk of CVDs among a peripheral rural Bangladeshi population and to explore the sociodemographic, anthropometric and clinical variables associated with increased risk. Study design: Cohort study. Methods: From a cohort of 190, 471 individuals of all ages, originally included in a diabetic eye disease program initiated in 2008–2009, a purposive sub-cohort of 66, 710 individuals, aged 31–74 years was recruited. During 2011–2012 these participants were assessed for CVDs using the WHO's risk assessment tool designed for primary care settings in low resource societies. Participant characteristics associated with higher risk were explored using univariable and multivariable regression analysis. Results: Out of all (95.5% participation rate) participants 1170 (1.84%) were found to be at high risk for CVD. The prevalence of hypertension (HTN), pre-HTN, obesity, underweight and self-reported DM were 8.9%, 15.2%, 9.6%, 7.8% and 0.5% respectively, among the study population. In multivariable regression analysis female sex, older age, temporary housing structure (i.e., tin shed), extremes of BMI (both underweight and obese) and central obesity were associated with higher risk for CVDs. Conclusions: The prevalence of CVD risk factors and high CVD risk individuals in this cohort was found to be lower than previous studies. It may be the effects of urbanization are yet to reach this relatively traditional rural population. This study adds to the literature on use of the WHO risk assessment tool. Highlights: Bangladeshis are prone to develop CVDs and the prevalence of the diseases among them are increasing rapidly. Ageing, higher socioeconomic status, smoking, hypertension, and diabetes are major risk factors for CVDs among urbanizing rural population. Using the WHO multiple risk factor assessment tool, the prevalence of high CVD risk individuals is low among a peripherally located rural Bangladeshi population. The prevalence of age, obesity, smoking and hypertension are low among a peripherally located rural Bangladeshi population. The level of urbanization should be carefully considered when analysing CVD risk factors in a specific study population.